Exploiting mixed conducting polymers in organic and bioelectronic devices. Issue 32 (9th August 2022) - Keene, Scott T.; Gueskine, Viktor; Berggren, Magnus; Malliaras, George G.; Tybrandt, Klas; Zozoulenko, Igor
Abstract : Mixed ionic-electronic conduction is a critical feature in a wide range of emerging electrochemical devices based on conjugated polymers exploiting transport, coupling, and charge carrier concentration modulation of both electronic and ionic charges. Abstract : Efficient transport of both ionic and electronic charges in conjugated polymers (CPs) has enabled a wide range of novel electrochemical devices spanning applications from energy storage to bioelectronic devices. In this Perspective, we provide an overview of the fundamental physical processes which underlie the operation of mixed conducting polymer (MCP) devices. While charge injection and transport have been studied extensively in both ionic and electronic conductors, translating these principles to mixed conducting systems proves challenging due to the complex relationships among the individual materials properties. We break down the process of electrochemical (de)doping, the basic feature exploited in mixed conducting devices, into its key steps, highlighting recent advances in the study of these physical processes in the context of MCPs. Furthermore, we identify remaining challenges in further extending fundamental understanding of MCP-based device operation. Ultimately, a deeper understanding of the elementary processes governing operation in MCPs will drive the advancement in both materials design and device performance.